Feasibility of collecting wound fluid during ongoing negative pressure wound therapy by the use of an additional container – A prospective observational study. Issue 5 (23rd December 2021) - Wolfsberger, Christina Helene; Maitz, Emanuel; Schmachtl, Philipp; Winkler, Sonja; Luschnig, Daniel; Sigl, Eva; Heinzle, Andrea; Gamerith, Clemens; Tuca, Alexandru‐Cristian; Schintler, Michael V.
Abstract: Negative‐pressure‐wound‐therapy is commonly used in clinical routine for wound management. Aim of the present study was to assess the feasibility and safety of using an additional container to collect wound fluid during ongoing negative‐pressure‐wound‐therapy. In this present prospective observational study, patients with negative‐pressure‐wound‐therapy were included. An additional container was inserted in the connecting tube between the wound and the vacuum generating device. The following 3 days, the container was changed daily and replaced by a new one. Further safety outcome parameters were assessed. A questionnaire was answered by the responsible surgeon. Twenty‐two patients with negative‐pressure‐wound‐therapy with a median (IQR) age of 58.5 (53.0‐70.0) years were included in the present study. In median, the duration of negative‐pressure‐wound‐therapy was 5.0 (4.6‐5.5) days. In mean ± SD the collected volume of the wound fluid in millilitres (mL) was on day one 7 ± 4 on day two 8 ± 7 and 10 ± 11 on day three. In one patient, there was <0.1 mL of clear water in the additional container. No safety concerns due to the additional container were observed. This study demonstrates that collecting wound fluid during ongoing negative‐pressure‐wound‐therapy over a time period of 3 days is feasible and safe. No safety concerns were observed.